Metabolite Changes After Metabolic Surgery – Associations to Parameters Reflecting Glucose Homeostasis and Lipid Levels - Ahlin, Sofie; Cefalo, Consuelo; Bondia-Pons, Isabel; Trošt, Kajetan; Capristo, Esmeralda; Marini, Luca; Romero, Montserrat; Zorzano, Antonio; Gastaldelli, Amalia; Mingrone, Geltrude; Nolan, John J. (Frontiers in Endocrinology, 2021)
Aims: To test the hypothesis that adipose tissue gene expression patterns would be affected by metabolic surgery and we aimed to identify genes and metabolic pathways as well as metabolites correlating with metabolic changes following metabolic surgery. Materials and methods: This observational study was conducted at the Obesity Unit at the Catholic University Hospital of the Sacred Heart in Rome, Italy. Fifteen patients, of which six patients underwent Roux-en-Y gastric bypass and nine patients underwent biliopancreatic diversion, were included. The participants underwent an oral glucose tolerance test and a hyperinsulinemic euglycemic clamp. Small polar metabolites were analyzed with a two-dimensional gas chromatography coupled to time-of-flight mass spectrometry (GC×GC-TOFMS). Gene expression analysis of genes related to metabolism of amino acids and fatty acids were analyzed in subcutaneous adipose tissue. All procedures were performed at study start and at follow-up (after 185.3 ± 72.9 days). Results: Twelve metabolites were significantly changed after metabolic surgery. Six metabolites were identified as 3-indoleacetic acid, 2-hydroxybutyric acid, valine, glutamic acid, 4-hydroxybenzeneacetic acid and alpha-tocopherol. The branched chain amino acids displayed a significant decrease together with a decrease in BCAT1 adipose tissue mRNA levels. Changes in the identified metabolites were associated to changes in lipid, insulin and glucose levels. Conclusions: Our study has identified metabolites and metabolic pathways that are altered by metabolic surgery and may be used as biomarkers for metabolic improvement.